Djungelboken en djurisk pekbok - Adams, Jennifer 1970-; Oliver, Alison (Bonnier Carlsen, 2017)
Introduces different animals using characters from Rudyard Kipling's "The jungle book."
At head of title: Unge Herr Kipling
Keywords: Kipling, Rudyard -- 1865-1936 -- The jungle book; Animals -- Juvenile fiction; Tiere; Bearbeitung; Board books; Bilderbuch